Changes in reservoir and motor-evacuatory function of the gallbladder in patients with asymptomatic cholecystolithiasis after organ-sparing surgery – laparoscopic cholecystolithotomy - D. V. Syvolap (Patologìâ)
Sonographic assessment of gallbladder structure and function in patients with gallstone disease needs further improvement not only to clarify the indications for organ-sparing operations such as laparoscopic cholecystolithotomy, but also to improve the results of surgical treatment of asymptomatic cholecystolithiasis by predicting probable restoration of motor-evacuatory function of the gallbladder and reduction of the number of recurrences of cholecystolithiasis.